A Discourse Analysis of Destructive Sociomental and Ethnocultural Constants in Taras Shevchenko’s Works (Based on “Kobzar”) - Melnyk, Yaroslav (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The article explores the constants in Taras Shevchenko’s poetry with a critical perspective on their functions in shaping a model of the world. The author attempts to give a systemic description of the constants and examines the poet’s interpretation of their characteristic features. In Taras Shevchenko’s poetic worldview, they gain systemic importance and are regarded as major obstacles to fostering national freedom, independence, and self-sufficiency. The approach allows for a somewhat different perspective not only on Taras Shevchenko’s oeuvre but also on Ukraine’s history and culture, as well as for new insights into the socio-cultural and political events of the last few decades. To date, linguists, literary critics, culturologists and other specialists have either regarded the categories under study as details of secondary importance or overlooked them altogether. This research project breaks some new ground in decoding Taras Shevchenko’s poetry